1993
DOI: 10.1300/j064v03n03_07
|View full text |Cite
|
Sign up to set email alerts
|

Weed Management in Spring Barley(Hordeum vulgare)in the Absence of Herbicides

Abstract: Field experiments were conducted in 1990 and 1991 at Scott, Saskatchewan to determine the effect of row spacing (11 22,33,46 cm) and seeding density (50,90,150,220 kg ha-') on thd. ability of spring barley to compete with weeds. Barley yield was greatest with narrow row spacings and increased seeding densities, however there was no spacing x density interaction. Biomass production of wild oats (Avena fatua L.), wild mustard (Brassica kaber (D.C.) L.C. Wheeler) and volunteer canola (Brassica campesrris L.)were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 0 publications
4
50
1
Order By: Relevance
“…However, observations made in this study confirm the conclusion of others (Berkowitz 1988;Kirkland 1993;Mohler 1996) that the higher stand seeding rates may improve crop competitive ability and consequently reduce the risk of problematic future weed infestations. Furthermore, the more rapid growth for the spring crop relative to the fall crop was also observed to suppress weed growth.…”
Section: Weed Managementsupporting
confidence: 90%
“…However, observations made in this study confirm the conclusion of others (Berkowitz 1988;Kirkland 1993;Mohler 1996) that the higher stand seeding rates may improve crop competitive ability and consequently reduce the risk of problematic future weed infestations. Furthermore, the more rapid growth for the spring crop relative to the fall crop was also observed to suppress weed growth.…”
Section: Weed Managementsupporting
confidence: 90%
“…compared with 67 kg ha -1 (Barton et al 1992); while increasing the barley seeding rate from 50 to 220 kg ha -1 resulted in yield increases ranging from 80 to 93% (Kirkland 1993). Prior to our study, there had been few attempts to derive a functional relationship between barley yield loss, and both wild oat and barley plant density using regression analysis.…”
Section: Estimating Barley Yield Loss and Economic Thresholdsmentioning
confidence: 98%
“…In conventional tillage systems, relatively high crop densities have been shown to reduce the impact of weeds on yield of wheat (Carlson and Hill 1985;Cudney et al 1989), barley (Evans et al 1991;Barton et al 1992;Kirkland 1993), and canola (O'Donovan 1994). Most of these studies also indicated that weed biomass and/or seed production decreased as crop density increased.…”
mentioning
confidence: 99%
“…Volunteer B. napus was one of the dominant species in the weed community in winter wheat following oilseed rape and was significantly related to the notillage treatment. Kirkland (1993) investigated the influence of barley (Hordeum vulgare L.) competition on biomass production of domesticated volunteer B. rapa in Saskatchewan and showed biomass reductions of 95% or more when barley was planted at 220 kg ha (1 in 11-cm rows compared with when barley was planted at 50 kg ha (1 in 46-cm rows. In an interference study between domesticated B. rapa and tartary buckwheat (Fagopyrum tataricum L.) where B. rapa was grown as the crop, O'Donovan (1994) found that B. rapa reproductive output was least affected at high B. rapa densities (200 plants m (2 ) compared with lower densities (50 and 100 plants m (2 ).…”
Section: Response To Other Human Manipulationsmentioning
confidence: 99%